2005
DOI: 10.1021/es050261e
|View full text |Cite
|
Sign up to set email alerts
|

Carbamazepine and Its Metabolites in Wastewater and in Biosolids in a Municipal Wastewater Treatment Plant

Abstract: Pharmaceutically active compounds (PhACs) are discharged into the environment from domestic wastewater treatment plants (WWTPs). In this study, we determined the distribution of the anti-epileptic drug, carbamazepine (CBZ), and its major metabolites and caffeine in both aqueous and solid phases through different treatment processes of a WWTP. A method was developed to extract samples of biosolids using pressurized liquid extraction (PLE), coupled with cleanup of extracts using solid-phase extraction. Samples o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
184
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 362 publications
(205 citation statements)
references
References 31 publications
17
184
1
3
Order By: Relevance
“…Indeed, pharmaceutical compounds are usually transformed in the liver or kidney to more polar and hydrophilic metabolites in order to be readily excreted in the urine or bile (Ikehata et al, 2006). For instance, the metabolite 10,11-dihydro-10,11-dihydroxycarbamazepine has a log K ow of 0.13 compared to 2.45 for the parent compound carbamazepine (Miao et al, 2005). Therefore, due to the low hydrophobicity of human metabolites, a lower PAC affinity is expected.…”
Section: Removal Efficiency With Higher Pac Dosementioning
confidence: 99%
“…Indeed, pharmaceutical compounds are usually transformed in the liver or kidney to more polar and hydrophilic metabolites in order to be readily excreted in the urine or bile (Ikehata et al, 2006). For instance, the metabolite 10,11-dihydro-10,11-dihydroxycarbamazepine has a log K ow of 0.13 compared to 2.45 for the parent compound carbamazepine (Miao et al, 2005). Therefore, due to the low hydrophobicity of human metabolites, a lower PAC affinity is expected.…”
Section: Removal Efficiency With Higher Pac Dosementioning
confidence: 99%
“…Finally, because of the large overlap between CBZ biotransformation and phototransformation metabolites/intermediates, the same compounds are produced by quite different processes. 1,[27][28][29][30][31] Largely out of this reason, to date there is no indication of which intermediates could be used as reliable markers of CBZ phototransformation in the environment. Therefore, it is presently not possible to distinguish between human metabolism, the (however limited) WWTP processing and photochemistry, as sources of CBZ intermediates in surface waters.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, removals based on combined loads were obtained for 562 carbamazepine and its two investigated metabolites, CBZ-DiOH and CBZ-EP. A limited number of 563 studies have investigated the removals of carbamazepine and its major metabolites in WWTPs 564 (Hummel et al, 2006;Leclercq et al, 2009;Miao et al, 2005). Only the study by Miao et al (2005) 565 examined the concentrations of carbamazepine and its metabolites at each treatment step of the 566 WWTP and observed a decline in the concentration of carbamazepine and its two metabolites in the 567 primary clarifier and an increase in carbamazepine and CBZ-DiOH concentrations by activated 568 sludge.…”
mentioning
confidence: 99%
“…The two metabolites of carbamazepine were not quantified in sludge 588 samples in the present study. However, Miao et al (2005) concluded that these compounds are 589 present at low concentrations in biosolids (<8 ng/g). 590 591 …”
mentioning
confidence: 99%